The Role of Apolipoproteins A1 and B as Prognostic Indicators in Progression of Breast Cancer - Sahar, Basim R.; Al-Jumaly, Rakad M. Kh (Iraqi Journal of Science, 2025)
Breast tumor is the most common lesion among women. This study was designed to investigate the role of apolipoproteins A1 and B (ApoA1 and B) as risk factors in the progression in blood serum of benign and malignant breast tumors patients. Commercial enzyme-linked immunosorbent assay (ELISA) kits were utilized to calculate apolipoproteins A1 and B levels in the serum of forty women with benign breast tumors (age range 16–65 years), forty women with malignant breast tumors (age range 33–75 years), and forty healthy women (age range 24 to 54 years) as a control group. The study included two groups of patients diagnosed with malignant breast tumors: stage II (low-level) and stages III and IV (high-level). The results of the current study showed a significant decrease (p< 0.05) in the levels of ApoA1 in patients with benign breast tumors and breast cancer (24.319±2.76 and 26.526±2.66 ng/ml, respectively) compared with the control group (32.89 ± 5.60 ng/mL). Also, the results of this study demonstrate there were no significant differences in the level of ApoB in women with benign breast tumors (4337 ±160 ng/ml) compared with the control group (4392±90.57 ng/ml) with a slight increase in the level of ApoB in women with malignant breast tumors (4603.9±102.4 ng/ml). Furthermore, there were no significant differences in levels of ApoA1 and ApoB in breast cancer patients at low-level and high-level stages compared to the control group. The results of the current study indicated that the concentrations of ApoA1 and ApoB in women's blood serum may be useful predictors for the early detection of breast cancer and serve as a prognostic indicator of its development.